Create From Zero – GNV Group Growth Journey - Tee, Chee Wee; Ng, Lee Peng; Choong, Yuen Onn; Kuar, Lok Sin; Teoh, Sok Yee; Chen, I-Chi (IIUM Journal of Case Studies in Management, 2025)
In 2011, Edward Lai, founded GNV Group Pvt. Ltd., aiming to provide an alternative to young couples with a garden wedding concept. However, bridging the mindset from traditional wedding styles to garden weddings took time. In the early days, Edward was lack of experience in dealing with the tenancy agreements resulted in escalating rental costs, forcing the company to relocate their business. By emphasising its corporate culture and core values of attention to detail, customer orientation and problem-solving, GNV successfully transformed the business, new wedding venues with different themes and a central kitchen were set up to meet the demands. This case study has two primary learning objectives. First, to understand the challenges and advantages GNV Group faced as a first mover in introducing garden weddings in Malaysia. Second, to analyse how GNV Group's core values—attention to detail, customer orientation, and problem-solving—shaped its business decisions and corporate culture. A qualitative approach was adopted, beginning with an in-depth interview with the founder, Edward Lai, to obtain firsthand insights into the company’s challenges, growth, and transformation. Additionally, secondary data was gathered from online articles, company websites, and industry reports to contextualize GNV’s role in the wedding industry and provide background on market trends and external challenges.